ENHANCING WRITING COMPREHENSION IN L2 ARABIC LEARNERS THROUGH AI-BASED TRANSLANGUAGING CHATBOTS - Rahmawati Zaimah, Nely; Fatchiatuzahro; Budi Hartanto, Eko (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2024)
The ability to speak a foreign language today is a skill that should be possessed by everyone, especially students, among whom are Arabic language skills. Nowadays, there are a lot of media and learning facilities that can be used to improve language skills. One of them is using AI chatbots, so this research is done to find out how effective these artificial intelligence chatbots are in improving the Arabic writing skills of L2 students. Second language acquisition poses a significant challenge when utilizing artificial intelligence chatbots for learning. Proficiency limitations in the second language can impede effective communication with chatbots. However, this challenge can be addressed through the practice of translanguaging in chatbot interactions. This study adopts a quantitative approach using pre-experimental methods to assess the efficacy of an artificial intelligence chatbot for enhancing Arabic writing comprehension within a translanguaging framework. The primary objective is to improve writing comprehension among Arabic learners as a second language (L2). The research involves 45 participants from Arabic language classes within the Department of Quranic Studies and Exegesis (IQT) at STAI Al-Anwar Sarang, Rembang. Statistical analyses and Bayesian inference are performed using JASP 0.18.1.0 software. Both classical and Bayesian analyses are employed to validate test results, augment probability and sustainability, while maintaining a focused analysis of the impact of chatbot-assisted learning within the translation framework. The results indicate a significant positive impact of utilizing AI chatbot-based Arabic writing comprehension among L2 learners. The researchers foresee the necessity for further exploration in the realms of translanguaging frameworks and their application in AI-assisted language learning